Buy-in or no buy-in? Teachers' perceptions of a school-based teacher learning approach in Singapore. (2019) - Wang, Li-Yi
Highlights: Teachers highly appreciated the long runway of PD. Teachers had different opinions of the quality of instructional leadership. Teachers recognized the potential of the approach in promoting teacher reflection. PD approach needs to provide a clearer focus of the topics of PD. PD approach needs to provide more concrete exemplars. Abstract: This study examines teachers' perceptions of a school-based professional development approach at a secondary school in Singapore. A thematic analysis of transcripts based on two focus group discussions with 10 teachers was conducted. The findings show that the participants appreciated the long runway of the approach but were uncomfortable with the curriculum-detached design of the approach. The participants had different opinions on the quality of instructional leadership but recognized the potential of the approach in promoting teacher reflection. The limitations include different levels of buy-in at the school, a backwash effect on students' learning outcomes, and insufficient formal learning platforms. The professional development approach needs to focus more clearly on PD topics and provide more concrete exemplars and reflective sharing.